Benzimidazolium salts bearing the trifluoromethyl group as organofluorine compounds: Synthesis, characterization, crystal structure, in silico study, and inhibitory profiles against acetylcholinesterase and α-glycosidase - Tezcan, Burcu; Gok, Yetkin; Sevincek, Resul; Taslimi, Parham; Taskin-Tok, Tugba; Aktas, Aydin; Guzel, Bilgehan; Taslimi, Parham (Wiley, 2022)
Here, we report the synthesis, characterization, and biological activities of a series of benzimidazolium salts bearing the trifluoromethylbenzyl group. All benzimidazolium salts were characterized by using nuclear magnetic resonance (NMR) (H-1 NMR and C-13 NMR), Fourier transform-infrared spectroscopy, and elemental analysis techniques. The crystal structures of some of these compounds were obtained by the single-crystal X-ray diffraction method. Furthermore, the acetylcholinesterase (AChE) and alpha-glycosidase (alpha-Gly) enzyme inhibition activities of these compounds were investigated. The obtained results revealed that 2e, with K-i value of 1.36 +/- 0.34 mu M against AChE and 3d with K-i value of 91.37 +/- 10.38 mu M against alpha-Gly, were the most potent compounds against both assigned enzymes. It should be noted that most of the synthesized compounds were more potent than standard inhibitor tacrine (TAC) against AChE. In silico studies, we focused on compound 2e, 3d, 3e, and 3f as potent inhibitors of AChE and alpha-Gly, the compound 2e showed good binding energy (-10.23 kcal/mol), among the three selected compounds and positive control (-10.18, -10.08, and -7.37 kcal/mol for 3d, 3f, and TAC, respectively). Likewise, as a result of the same compounds against the alpha-Gly enzyme, the compound 3d had the highest binding affinity (-8.39 kcal/mol) between the four selected compounds and the positive control (-8.27, -8.10, -8.06, and -7.53 kcal/mol for 3f, 3e, 2e, and acarbose, respectively). From the absorption, distribution, metabolism, excretion, and toxicity analyses, it can be concluded that the compounds under consideration exhibited more drug-likeness properties in the prediction studies compared to positive controls.
Keywords: Acetylcholinesterase; Benzimidazolium Salt; In Silico Study; Trifluoromethyl; Alpha-Glycosidase